1990
DOI: 10.1113/jphysiol.1990.sp018190
|View full text |Cite
|
Sign up to set email alerts
|

Induced neural‐type differentiation in the cleavage‐arrested blastomere isolated from early ascidian embryos.

Abstract: SUMMARY1. Isolated blastomeres and pairs of blastomeres from 8-cell embryos of Halocynthia roretzi and Halocynthia aurantium were cleavage-arrested with cytochalasin B and cultured. Their differentiation was examined in terms of membrane excitability, immunoreactivity to an epidermis-specific monoclonal antibody (2C5), and the presence of acetylcholinesterase.2. The blastomeres that showed epidermal-type differentiation had Ca2+-dependent action potentials and membrane currents, and immunoreactivity to 2C5. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 23 publications
7
56
0
Order By: Relevance
“…Previous work in our laboratory (Okado & Takahashi, 1990b) has shown that neural differentiation was induced by cell contact with the blastomere, A4-1, which contains the presumptive notochordal area, only if contact occurred before the late gastrula stage; the same critical period existed when neural differentiation was induced by protease (Okado & Takahashi, 1990b, 1993.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work in our laboratory (Okado & Takahashi, 1990b) has shown that neural differentiation was induced by cell contact with the blastomere, A4-1, which contains the presumptive notochordal area, only if contact occurred before the late gastrula stage; the same critical period existed when neural differentiation was induced by protease (Okado & Takahashi, 1990b, 1993.…”
Section: Discussionmentioning
confidence: 99%
“…From previous studies (Okamura & Shidara, 1990a, b), it is known that most of the inward current is generated through the biexponentially inactivating-type Na+ channel, which is distinct from the fast-inactivating Na+ channel expressed at earlier stages. Long-lasting Ca2+ currents were also expressed in neural differentiation (Hirano & Takahashi, 1984;Okado & Takahashi, 1990b), although, in the solution we used, the contribution of the long-lasting-type Ca2+ current to the inward current was negligible, compared with that of the Na+ current. Outward currents were the currents through a TEA-sensitive type of the delayedrectifier K+ channel which can be distinguished from the channel of the musculartype cell on the basis of both kinetics and TEA sensitivity (Shidara & Okamura, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations